Efektivitas Penerapan Model Pembelajaran Think Talk Write (TTW) Secara Online Terhadap Literasi Informasi Siswa SMA - I Putu Artayasa; Tia Fitriani; Baiq Sri Handayani; Kusmiyati Kusmiyati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to analyze the effectiveness of the Think Talk Write (TTW) learning model which is carried out online on the information literacy of high school students. This study used a quasi-experimental method with a non-equivalent control group pretest-posttest design. The study was conducted on students of class XI IPA SMA Negeri 1 Labuapi consisting of 36 people. Research data were in the form of information literacy scores obtained from the application of pretest and posttest. The data analysis technique used in this study was covariance analysis (ancova). The results showed that the class that applied TTW learning had an average information literacy posttest score of 3.26 which was higher than the conventional class with an average gain of 2.97. The conclusion is that the application of the TTW learning model is more effective than the conventional learning model in terms of achieving student information literacy.